Policy recommendations for the Rana trade towards the Republic of Korea - Borzée, Amaël; Rodriguez, Maribel; Bhatri, Naila; Kim, Ye Inn; Angulo, Ariadne; Kim, Daemin; Chang, Min-Ho; Sung, Ha-Cheol; Heo, Kyongman; Park, Il-Kook; Song, Jae-Young; Jung, Ji-Hwa; et al. (Frontiers in Environmental Science, 2023)
- Ban the trade of non-native species for consumption as food or derived products and for personal use (i.e pet keeping) - Ban the trade of native species when they do not originate from within the nation (i.e. same genetically defined conservation unit) - Tracking of potential established alien Rana populations - Eradication of potentially established alien Rana populations